A reabilitação do consumidor à vida política: um diálogo entre Hannah Arendt e a política nacional das relações de consumo - TEIXEIRA, Alex’a Negrão (2024)
This work aims to establish a dialogue between Hannah Arendt's writings and the National Consumer Relations Policy, analyzing its potential as a catalyst for action and discourse within the social sphere as a means to confront the alienation from the world, characterized by isolation, loneliness, conformity, indolence, and conditioned behavior. The research was conducted using bibliographic methodology with a qualitative and descriptive approach. Arendtian concepts of "active life" were analyzed in parallel with the principles and norms relevant to the consumer protection structure in Brazil. The conclusion drawn is that it is both necessary and possible to rehabilitate consumers to political life through the revaluation of spaces for qualified action, with emphasis on the Collective Convention as an instrument that promotes dialogue and mutual commitment, essentially political elements.